Convenient Access to Carbohydrate–BODIPY Hybrids by Two Complementary Methods Involving One‐Pot Assembly of "Clickable" BODIPY Dyes (Eur. J. Org. Chem. 26/2014). Issue 26 (September 2014) - Martinez‐Gonzalez, Mayra R.; Urías‐Benavides, Arlette; Alvarado‐Martínez, Enrique; Lopez, J. Cristobal; Gómez, Ana M.; del Rio, Mayca; Garcia, Inmaculada; Costela, Angel; Bañuelos, Jorge; Arbeloa, Teresa; Lopez Arbeloa, Iñigo; Peña‐Cabrera, Eduardo
Abstract : The cover picture shows two concise, complementary, protocols for the one‐pot, three‐component assembly of an alkyne‐ or azido‐carbohydrate, 8‐thiomethyl BODIPY, and either propargylamine or an azido boronic acid, respectively, which allow access to fluorescent carbohydrate–BODIPY hybrids. These carbohydrate–BODIPY hybrids display excellent photophysical and laser properties that relate to the spacer employed (amino group or aromatic ring). Details are discussed in the Short Communication by J. C. Lopez, J. Bañuelos, E. Peña‐Cabrera et al. on p.5659 ff .